BODY IMAGE OF YOUNG ADULT WOMEN WITH BODY SHAMING EXPERIENCE IN THE FITNESS CENTER OF MALANG CITY - Tien Aminah; Alfunnafi Fahrul Rizzal; Purnomo Retno Palupi Widya; Apriyani Puji Hastuti; Bayu Budi Laksono (Indonesian Journal Of Empirical Nursing Sciences, 2024)
Young adult women are victims of body shaming or critics regarding skins color, and body size. A person who have negative image because she only focused on self - image, not recognizing his own strength and potential. A negative self - image refers too much to other people's assessment of themselves, hows judge their body image or their physical condition The design of this study used descriptive study with cross - sectional approaches . The population of study are women of early adulthood . The sampling technique used consequence sampling with 60 samples size . Variables of this study was body image of young adult women . Instruments of this study using questionnaire . Analysis of this study used univariate analyzed. The results of this study shows that of body image disturbance 90% and less body image disturbance 10%. These results are influenced by several factors , age , gender , marital status, community and experience of body shaming . Based on this research, it can motivate that early adult women can develop a positive self - concept so that they will create satisfaction with their positive body image and positive coping mechanisms .